DINAMIKA HARIAN PLANKTON DI TELUK PANGPANG BLOK JATI PAPAK TAMAN NASIOAL ALAS PURWO - Nasuka, Nurul Alfiyatun; As’ari, Hasyim; Kurniawan, Ridho; Ardiyansyah, Fuad; Nurmasari, Fitri (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2024)
National Park Alas purwo is one the conservation areas have a fairly extensive mangrove forest and one of them is the area Bay Pangpang Blok Jati Papak. Mangrove forest have many functions that many marine organisms that occupy the regions one of the region one of which is plankton. Plankton are organisms that are generally relatively small size and its movement depends on the direction of water flow. Plankton are organisms that are generally relatively small size and its movement depends on the direction of water flow. This study aims to determine the abundance and dynamics of plankton daily in at Bay Pangpang Block Jati Papak Nasional Park Alas Purwo. This study was conducted in May-June, 2016. The method used in this research is purposive sampling to determine the point where the (station), and sampling performed every 2 hours over a period of 24 hours. Abiotic parameters include measurements temperature, pH and light penetration. The research found that 13 spec Nitzchia sp, Oedogonium sp, Vaucheria sp, Eretmocaris, Dracia moluska, Amfipod, Micracia, Glaucothoe peroni, Candacia truncata, Candacia curta, Subbeucalamus crassus, Candacia bradi dan Undinula vulgaris. The highest abundanc species of phytoplankton that Nitzchia sp, while the highest abundance of zooplankton that is Candacia truncata species. The highest dynamics of plankton occurs at the time of sampling 07.00 dean in the number of species found are 7 to fotoplankton species and 16 species of zooplankton.